ANALISIS KINERJA KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN PURWOREJO TAHUN 2018-2020 - Tyas, Fauziah Ayu Setyaning; Rani, Utpala (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to analyze the performance of the Regional Revenue and Expenditure Budget (APBD) of Purworejo Regency in terms of financial ratios for 2018-2020. This study uses a quantitative descriptive analysis method, with data in the form of secondary data, namely the Purworejo Regency Regional Budget Realization Report 2018-2020 obtained from the purworejokab.go.id website. The data were analyzed using financial ratios, including: analysis of regional income variance, analysis of the ratio of regional independence, analysis of effectiveness on PAD, as well as an analysis of efficiency ratios. The results of the study highlight that the financial performance of the Purworejo Regency Regional Revenue and Expenditure Budget for 2018-2020 is said to be good, which can be seen from the regional income variance with an average of 100.53%. Nevertheless, the level of independence is still very low with an average of 13.65%, but the PAD effectiveness ratio and PAD efficiency ratio analysis in Purworejo district are very effective and efficient with an average analysis of 104.8% and 93.57%, respectively.